Marble in Oesophagus of Neonate: A Unique and Unprecedented Case Report - Ehtesham, H.N. Sayyed; Beg, Mohammed Haneef; Haseen, Azam; Akhtar, Sadik (International Journal of Pediatrics and Child Health, 2015)
One of the most serious causes of morbidity and mortality in children below 5 years of age are swallowed and inhaled foreign bodies. Children of age 5month – 8years are at vary high risk of foreign body ingestion. Ingestion of foreign body in neonatal period is although rare. We here by describe a 21-day-old neonate who had a large sized spherical glass marble impacted in the cervical oesophagus for a long period. The foreign body was successfully removed by rigid oesophagoscopy. The case is discussed as it was first large sized spherical glass marble to be impacted and removed from cervical oesophagus of a neonate which has not been earlier reported in world English literature.